2013
DOI: 10.1128/jb.02134-12
|View full text |Cite
|
Sign up to set email alerts
|

FtsH-Mediated Coordination of Lipopolysaccharide Biosynthesis in Escherichia coli Correlates with the Growth Rate and the Alarmone (p)ppGpp

Abstract: The outer membrane is the first line of defense for Gram-negative bacteria and serves as a major barrier for antibiotics and other harmful substances. The biosynthesis of lipopolysaccharides (LPS), the essential component of the outer membrane, must be tightly controlled as both too much and too little LPS are toxic. In Escherichia coli, the cellular level of the key enzyme LpxC, which catalyzes the first committed step in LPS biosynthesis, is adjusted by proteolysis carried out by the essential and membrane-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 80 publications
4
75
1
Order By: Relevance
“…Consistent with the cellular demand, degradation of LpxC negatively correlates with the growth rate, i.e. the enzyme is stable during fast growth and rapidly degraded when cells grow slowly ( Figure 1B) (Schäkermann et al, 2013). A factor that is involved in growth-rate dependent turn-over of LpxC is the alarmone (p)ppGpp (Schäkermann et al, 2013).…”
Section: Conditional Proteolysis Of Selected Ftsh Substrates Lpxc Thmentioning
confidence: 79%
See 2 more Smart Citations
“…Consistent with the cellular demand, degradation of LpxC negatively correlates with the growth rate, i.e. the enzyme is stable during fast growth and rapidly degraded when cells grow slowly ( Figure 1B) (Schäkermann et al, 2013). A factor that is involved in growth-rate dependent turn-over of LpxC is the alarmone (p)ppGpp (Schäkermann et al, 2013).…”
Section: Conditional Proteolysis Of Selected Ftsh Substrates Lpxc Thmentioning
confidence: 79%
“…the enzyme is stable during fast growth and rapidly degraded when cells grow slowly ( Figure 1B) (Schäkermann et al, 2013). A factor that is involved in growth-rate dependent turn-over of LpxC is the alarmone (p)ppGpp (Schäkermann et al, 2013). (p)ppGpp, best known for its role in the stringent response, is involved in regulating many processes in response to various stress and starvation signals (Potrykus and Cashel, 2008;Gaca et al, 2015).…”
Section: Conditional Proteolysis Of Selected Ftsh Substrates Lpxc Thmentioning
confidence: 99%
See 1 more Smart Citation
“…S2F). LpxC is known to be regulated by FtsH-mediated proteolysis (23), and thus we suspect that the mlaA* mutation stabilizes the LpxC protein (likely indirectly), resulting in increased synthesis and assembly of LPS in this mutant background.…”
Section: Resultsmentioning
confidence: 99%
“…The alarmone (p)ppGpp is involved in the regulation of fatty acids and lipopolysaccharide synthesis in E. coli (5,51,52). Recently, it was shown that c-di-GMP binds to a transcription factor, LtmA, that regulates the expression of genes involved in lipid transport in M. smegmatis (21).…”
Section: Figmentioning
confidence: 99%